Respuesta :
Answer:
y = -2x + 10
use the following formula:
y₁ - y = m ( x₁ - x )
using this formula:
[tex]\hookrightarrow[/tex] y₁ - y = m ( x₁ - x )
[tex]\hookrightarrow[/tex] y - -4 = -2 ( x - 7 )
[tex]\hookrightarrow[/tex] y + 4 = -2 ( x - 7 )
[tex]\hookrightarrow[/tex] y = -2x + 14 -4
[tex]\hookrightarrow[/tex] y = -2x + 10
Answer:
[tex]\mathsf{y=-2x+10}[/tex]
Step-by-step explanation:
slope-intercept form of a linear equation: y = mx + b
(where m is the slope and b is the y-intercept)
point-slope form of a linear equation: [tex]\mathsf{y-y_1=m(x-x_1)}[/tex]
(where m is the slope and [tex]\mathsf{(x_1,y_1)}[/tex] is the point)
Given:
- m = -7
- [tex]\mathsf{(x_1,y_1)=(7,-4)}[/tex]
Substitute these values into the point-slope equation:
[tex]\mathsf{y--4=-2(x-7)}[/tex]
[tex]\mathsf{y+4=-2(x-7)}[/tex]
Now rearrange to put into slope-intercept form by making y the subject:
[tex]\mathsf{y+4=-2x+14}[/tex]
[tex]\mathsf{y=-2x+10}[/tex]